1988
DOI: 10.1093/infdis/157.3.536
|View full text |Cite
|
Sign up to set email alerts
|

Onchocerciasis and Immunity in Humans: Enhanced T Cell Responsiveness to Parasite Antigen in Putatively Immune Individuals

Abstract: To identify possible immune mechanisms in human onchocerciasis, we compared a group of 12 individuals who had no clinical or parasitological evidence of infection, despite ongoing exposure to the parasite, with a group of 16 individuals from the same area who had active Onchocerca volvulus infection. Despite having less parasite-specific serum antibody, the infection-free ("putatively immune") individuals showed greater lymphocyte responsiveness, especially interleukin-2 (IL-2) production, to O. volvulus antig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 14 publications
6
81
0
Order By: Relevance
“…In regions that are hyperendemic for O. volvulus, human PI subpopulations have been identified in both West Africa (20) and Latin America (21). This phenomenon has been the focus of intensive immunological study (8)(9)(10)22), and although several characteristic features have been identified in PI, including a discrete distribution of HLA-D alleles (20), it has not been possible to categorically exclude the influence of risk factors such as occupation, social status, and migration. A human bait catch study conducted in Guinea concluded that PI and those with generalized onchocerciasis did not differ significantly in vector attractiveness, although fly catches were performed over a single 2-day period, and the vectors were caught before biting for ethical reasons (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In regions that are hyperendemic for O. volvulus, human PI subpopulations have been identified in both West Africa (20) and Latin America (21). This phenomenon has been the focus of intensive immunological study (8)(9)(10)22), and although several characteristic features have been identified in PI, including a discrete distribution of HLA-D alleles (20), it has not been possible to categorically exclude the influence of risk factors such as occupation, social status, and migration. A human bait catch study conducted in Guinea concluded that PI and those with generalized onchocerciasis did not differ significantly in vector attractiveness, although fly catches were performed over a single 2-day period, and the vectors were caught before biting for ethical reasons (12).…”
Section: Discussionmentioning
confidence: 99%
“…Pregnant Gudali cows were recruited from the area around Ngaoundéré, and their calves were reared in fly-proof accommodations from birth. The calves were assigned to two groups, vaccinated (n ϭ 9) and control (n ϭ 13), which were matched for age at the start of immunization [median (range) ϭ 12 (7)(8)(9)(10)(11)(12)(13)(14) weeks for the vaccinated group and 11 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16) weeks for the controls] and O. ochengi infection status of the dams (67% Mfpositive for the vaccinated group and 77% for the controls).…”
Section: Vaccine Preparation and Protocol (Expsmentioning
confidence: 99%
See 1 more Smart Citation
“…these patients were treated again with the same dose, and were subsequently rc-trcated with 150 /ig/kg at intervals of 12-18 months. The second group of patients (Group 2, n = 51) initially received placebo, but these individuals were treated with ivermectin (150 /ig/kg) at 22 months and subsequently in the same intervals as Group I, Group 3, which was established in 1989, consisted of 61 previously untreated onchocerciasis patients who annually received ivermectin (150 /ig/kg) [14], A group of local individuals who were exposed to O. votvutus infective larvae-but who exhibited no microfilariae in skin biopsies and had had no previous anti-filarial therapy--will be referred to as 'endemic normals' [11].…”
Section: Patients and Control Individualsmentioning
confidence: 99%
“…parasite O. volvulus demonstrate not only a prominent produc-tion of all subclasses of parasite-specific immunoglobulins [7,8],, bui also depressed cellular reactivity in vitro and deficient production of IL-2 in response to O. rfl/vu/uj-specific antigenic (OvAg) stimulation [9][10][11], Recent reports suggest that ivermectin temporarily eliminates microfilariae (mO from the skin and ;ilso facilitates cellular immunity in treated patients [12][13][14]. However, whether onchocerciasis-associated immunosuppression in patients may gradually be converted into an effective immune response remains unanswered.…”
Section: Introductionmentioning
confidence: 99%